Phonetic-phonological analysis of the processes affecting the occlusive segments in the coda position in the spanish of Lima - Cueva Sánchez, Óscar Esaul (2018)
This paper is intended to give a synchronic description of the phonological processes suffered by the occlusive segments in coda position at the inner part of the word in the Spanish of Lima. In addition, the descriptive part of the research will be supported by acoustic data that may be evidenced throughout the work. For this purpose the Praat program was used (acoustic analysis). On the other hand, the contrast between the onset and syllabic coda is evidenced from the types ofprocesses that affect each of these positions; for example, the onsets tend to be modified by reinforcement phenomena, while the syllabic codas are modified by weakening processes. Precisely, the purpose ofthis work is to give account of these weakening processes affecting the occlusive segments in syllabic coda. Likewise, for the explanatory part of this paper, the non-linear generative phonology will be used as a theoretical framework.